The role of beach ridges, spits, or barriers in understanding marine terraces processes on loose or semiconsolidated substrates: Insights from the givoni of the Gulf of Taranto (southern Italy). (5th July 2019) - De Santis, Vincenzo; Caldara, Massimo; Torres, Trinidad; Ortiz, José E.; Sánchez‐Palencia, Yolanda
Abstract : This paper presents a detailed geological and geomorphological analysis of the so‐called givoni (low‐relief, mainly gravelly landforms subparallel to the coastline) associated with the MIS 5 terrace in the northern Gulf of Taranto (southern Italy). These landforms can be interpreted as former beach ridges, swash/drift‐aligned spits, or swash/drift‐aligned barriers (BSBs); thus, givoni are palaeoshoreline indicators. In the study area, recognizing the classic landforms associated with marine terraces, that is, surfaces and scarps, is difficult, as the givoni are often associated and variably combined with surfaces and scarps. Thus, we reconstruct the formation and evolution processes of the MIS 5 marine terrace, including the formation of surfaces, scarps, and BSBs (and the resulting composite landforms), in an overall evolutionary framework based on eustatic oscillations. Then, we reconstruct a complete set of situations in which BSBs form on loose or semiconsolidated substrates in response to eustatic oscillations: (a) BSBs can form during a highstand of a warm stage on previously consolidated sediment; (b) BSBs may represent coastlines formed during sea‐level standstills in the context of a general regressive phase following the highstand peak that created a relict sea cliff; (c) BSBs may represent coastlines formed during a new relative highstand in a warm substage on previously unconsolidated deposits formed during the same stage; and (d) BSBs may be formed by a process similar to that of the previous case, except that the sea level stopped rising against a pre‐existing BSB.